Development Model of the Inverter Size for the GCC Countries - Qamber, Isa Salman (Applications of Modelling and Simulation, 2021)
It is important to develop a suitable model to find the suitable design of inverter based on a required specification that needed to calculate the number of units per day requested by the house holders or companies. The present study deals with the required design using a developed Adaptive Neuro-Fuzzy Inference System (ANFIS) method and based on the calculated results the curve fitting is applied to form the suitable formula. The model is formulated as a function of number of units per day for the Gulf Cooperation Council (GCC) region. In general, the GCC region has high-energy consumption influenced by several factors. Therefore, the solar energy is helping to reduce the use of gas or other fuels to generate power. This means that the obtained results will encourage the GCC through the energy field development and setting the future for it to increase the use of solar energy production. The novelty of the present study is to avoid an increase in generation capacity using the gas to produce the electricity. In addition, it will help the GCC countries to avoid load shedding and meet the energy demands in different sectors. Furthermore, the developed model will help the economic development of the GCC countries. These results reduce capital investment, limiting the equipment installed and the expected load needed in the region.